Circulating cassettes of ceremony: Indigenous peer-to-peer networks in Arnhem Land. - Lazarus, Robert (Media, Culture & Society, 2022)
During the late 1970s, audio cassette technology became freely available in the Northern Australian Aboriginal reserve of Arnhem Land. Made for easy production and dissemination, magnetic tapes were loaded into mobile decks by clan leaders and distributed across the region. The transfer of clan-based knowledge using tape technologies built a rich collection of cultural records featuring ceremonial activity. The focus of this paper is not the content – what was recorded, but how ceremonial leaders employed hundreds of tapes to produce documentation in specific ways. Media theory is placed in a non-western historical context. I examine how a cassette library built by Indigenous peer to peer networks in Arnhem Land documents the media culture of a ceremonial society. A theory of ceremonial communication systems displays Arnhem Lands continuous and contemporary media history. I argue the circulation of cassettes extends movable media traditions in Indigenous Australia and formats new media practices now occupied by digital devices.